GPAT2 is required for piRNA biogenesis, transposon silencing, and maintenance of spermatogonia in mice†. Issue 1 (5th April 2019) - Shiromoto, Yusuke; Kuramochi-Miyagawa, Satomi; Nagamori, Ippei; Chuma, Shinichiro; Arakawa, Tatsuhiko; Nishimura, Toru; Hasuwa, Hidetoshi; Tachibana, Taro; Ikawa, Masahito; Nakano, Toru
Abstract: PIWI-interacting RNAs (piRNAs), a subclass of germ cell-specific noncoding small RNAs, are essential for de novo DNA methylation of retrotransposon genes in embryonic testes. PIWIL2/MILI, one of three mouse PIWI family members, is indispensable for piRNA production, DNA methylation of retrotransposons presumably via piRNA, and normal spermatogenesis. In vitro analysis using germline stem cells (GS cells) revealed that glycerol-3-phosphate acyltransferase 2 (GPAT2), which is a mitochondrial outer membrane protein involved in generation of lysophosphatidic acid (LPA) and highly expressed in testes, plays important roles in spermatogenesis. Namely, GPAT2 binds to PIWIL2 and is closely involved in the biogenesis of piRNAs; this process is independent of its enzymatic activity on LPA. However, GS cells recapitulate only a limited phase of spermatogenesis and the biological functions of GPAT2 remain largely unknown. In this study, we generated GPAT2-deficient mice and conducted comprehensive analyses. The deficient mice showed defective piRNA production and subsequent de-silencing of IAP and Line-1 retrotransposons in fetal testes. In addition, apoptosis of pachytene spermatocytes was observed. These abnormalities were all common to the phenotype of PIWIL2-deficient mice, in which piRNA production was impaired. GPAT2-deficient mice exhibited apoptosis in spermatogonia at the neonatal stage, which was not observed in PIWIL2-deficient mice. These data show that GPAT2 plays a critical role in preventing apoptosis in spermatogonia. Abstract : GPAT2-deficient mice showed that GPAT2 was essential for piRNA production and subsequent retrotransposon gene silencing by DNA methylation, and that apoptosis of neonatal spermatogonia and pachytene phase spermatocytes were induced by the mutation.